FORECASTING ALGORITMA REGRESI LINIER PADA PEMBERANGKATAN UNIT LUAR PULAU UNTUK MEMPREDIKSI JANGKA WAKTU PENERIMAAN UNIT AC - Randy Nurmanto; Hidayatullah Al Islami (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
In the era of Global Warming like now Air Conditioner is something that is quite important to control the room temperature to stay cool and comfortable, this can be seen in every modern store that mushrooms almost all use air conditioning. PT. XYZ as a company whose core business is rental and service Air Conditioner distributes Air Conditioner in every modern store following the expansion of modern stores, this causes shipping also following the expansion of modern stores. The distribution of units is carried out using cargo that still has both internal and external factors in each shipment that cause delays in units until the time of installation. The purpose of this study is to provide information in the form of predictions of unit estimates to help in planning and supervising the delivery of Air Conditioner units. The method used in this study is Forecasting with Simple Linear Regression algorithm, this method will manage quantitative data which will produce output in the form of predictions against until unit estimates. The results of this method which uses two delivery objects, namely Samarinda and Medan, Samarinda are known to have an accuracy rate of 90.25% prediction results with a MAPE value of 9.75% which can be categorized as very feasible to use. While the terrain delivery is known to have an accuracy rate of 79.13% prediction results with a MAPE value of 21.87% which can be categorized as quite feasible to use. So that the information generated from the results of prediction calculations with the Simple Linear Regression algorithm Forecasting method can be used.